Perubahan Aktivitas Antioksidan, Kadar Antosianin dan Polifenol pada Beberapa Tingkat Kemasakan Buah Duwet (syzygium Cumini) - Lydia Ninan Lestario; Suparmo Suparmo; Sri Raharjo; Tranggono Tranggono (agriTECH, 2005)
Research on antioxidant activity, anthocyanin, and polyphenol contents of Java plum (Syzygium cumini) from several stages of maturity was carried out with three aims: to prove that the fruit contain anthocyanins; to compare antioxidant activity from three stages of fruit maturity; and to examine the possible correlation between maturation and antioxidant activity, anthocyanin and polyphenol contents. The fruit pulp was separated from the seed, frozen dried, and kept in freezer. The freezer dried fruit was extracted (macerated) with methanol-HCl 1% for overnight at 4ºC, and filtered with Whatman no 1 to obtain fruit extract. Anthocyanin-betacyanin testing was used to indicate that the fruit contain anthocyanin. Antioxidant activity test was conducted with ferri-thiocyanate method in linoleic acid emulsion system. Anthocyanin contents was determined with pH differential method, while its polyphenol with spectrophotometric method with Folin-CIocalteu reagent. The result showed that the fruit contained anthocyanin, ranging from 1,68 mg/g at young stage (green) to 29,39 mg/g at overripe stage (black), and showed that antioxidant activity was influenced by fruit maturity. With regard to fruit maturoty, the antioxidant activity of purple, red, adn green fruit were 64,75%, 62,42%, and 29,86% respectively; whereas that of BHT was 79,45%. It was noted that there were significant correlation between the level of anthocyanins, poluphenols, and the degrees of maturity. As the fruit maturity increased, the anthocyanin increased, but the polyphenol decreased. The fruit contained considerable amount of anthocyanins and had antioxidant activity that was influenced by stages of maturity. It was indicated that the more mature the fruit the higher anthocyanins and the lower polyphenols concentrations.